2D NMR assisted structure elucidation of three cyanoethylated cellulose derivatives and correlated with their properties. (January 2020) - Zhang, Yan; Shen, Xiaofei; Qian, Hao; Song, Lei; Xie, Kaiyun; Zhang, Mingtao; Wang, Huiqing
Abstract: Three cellulose derivatives CEC, CEHEC, and CEGEC prepared by cyanoethylation of cellulose, hydroxyethyl cellulose (HEC), and glycerol ether cellulose (GEC), respectively, with similar degrees of substitution, exhibited different properties involving their dielectric application. But their structures were hard to distinguish by FTIR, 1 H NMR, or 13 C NMR spectroscopy. Here, 2D NMR techniques (COSY, HSQC) assisted by partial hydrolysis and full acetylation were applied and demonstrated to be useful for structural elucidation, differentiated their peaks on 2D NMR map. Furthermore, GPC-MALLS revealed that CEHEC has highest branching ratio, while CEC was strictly linear with similar molecular weights. Branching CEHEC exhibited a lowest Tg, while CEGEC showed better dielectric properties due to the relative mobility of the cyano groups at the end of the glycerol moieties. So this work open the way of exploring structure of carbohydrate polymer derivatives assisting by 2D NMR techniques COSY and HSQC. Graphical abstract: Image 1 Highlights: It's impossible to distinguish structures of CEC, CEHEC, and CEGEC by 1 H or 13 C NMR. 2D-NMR after hydrolysis and acetylation were applied for structural elucidation. GPC-MALLS revealed CEHEC is branching structure, while CEC was strictly linear. CEGEC showed better dielectric properties due to mobility of CN at end of glycerol. Open the way of exploring structure of cellulose mix ether derivatives by 2D-NMR.